STUDI BIBLIOMETRIK DAN SEBARAN TOPIK KOLEKSI KHUSUS BAGI CIVITAS AKADEMIKA STAIN AL-FATAH JAYAPURA TAHUN 2007-2017 (SEKARANG IAIN FATTAHUL MULUK PAPUA) - Tuwaji Tuwaji (Perpustakaan Nasional RI, 2019)
This study of bibliometric and topic distribution of special collection of STAIN Al Fatah Jayapura Library covered scientific books written by lecturers, research reports, articles of Jabal Hikmah Journal, undergraduate theses, master theses, directories, proceedings and scrapbooks. The discussion covered the following aspects: 1). Topics had not been evenly distributed: there are fields of science that are frequently written, such as Islamic education, Qur'an literacy, learning methodology, teaching process and teacher. Meanwhile, the fields of science that are rarely written are discussions of curriculum, tolerance in Islam, students, education and guidance systems. 2). Writer's productivity; the most productive book writers were Idrus Al Hamid and Umar Faruq with 11 titles. The most productive research writer was Sofwan Aljauhari with 3 titles. The most productive Jabal Hikmah’s article writer were Idrus Al Hamid and Safiudin with 4 titles. The fluctuation of the number of special collections totaled 511 titles. 3). The degree of collaborative writing remained very low. Of this title’s number, 21 titles were written by multiple writers (4.07%), the remaining 490 titles (95.07%) by single writers. The degree of collaboration in the collection of scientific-book writings was (0.6) and of research reports was (0.38). 4). The use of references was low, it means that some of the literatures or book references used had been repeatedly used and some were newly published. Regarding the latest reference data used, 34% of them were 0-5 years old, 38% of them were 6-10 years old, and references that had higher obsolescence level, they had lower level of usageThis study of bibliometric and topic distribution of special collection of STAIN Al Fatah Jayapura Library covered scientific books written by lecturers, research reports, articles of Jabal Hikmah Journal, undergraduate theses, master theses, directories, proceedings and scrapbooks. The discussion covered the following aspects: 1). Topics had not been evenly distributed: there are fields of science that are frequently written, such as Islamic education, Qur'an literacy, learning methodology, teaching process and teacher. Meanwhile, the fields of science that are rarely written are discussions of curriculum, tolerance in Islam, students, education and guidance systems. 2). Writer's productivity; the most productive book writers were Idrus Al Hamid and Umar Faruq with 11 titles. The most productive research writer was Sofwan Aljauhari with 3 titles. The most productive Jabal Hikmah’s article writer were Idrus Al Hamid and Safiudin with 4 titles. The fluctuation of the number of special collections totaled 511 titles. 3). The degree of collaborative writing remained very low. Of this title’s number, 21 titles were written by multiple writers (4.07%), the remaining 490 titles (95.07%) by single writers. The degree of collaboration in the collection of scientific-book writings was (0.6) andspan style=